Latest trends, challenges and solutions in security in the era of cloud computing and software defined networks - Wajid Hassan; Te-Shun Chou; Xiaoming Li; Patrick Appiah-Kubi; Tamer Omar (International Journal of Informatics and Communication Technology (IJ-ICT), 2019)
The emergence of cloud computing has changed perception of all regarding software delivery, development models and infrastructure. Cloud computing has a potential of providing elastic, easily manageable, powerful and cost effective solutions. The rapid transition to cloud computing has fueled concerns on the security issues. The migration of the user’s data and applications in a shared environment of a cloud, where there is a collocation of several users increases security related concerns. Several research efforts have been made in evaluating challenges related to security faced by the cloud computing environments, a number of solutions of such problems have also been proposed. Integrated security solutions should be devised to deal with the increasing security risks. In this paper, a detailed cloud computing survey, key services and concepts are being presented.  This paper attempts to evaluate various security threats to cloud computing and a number of security solutions have also been discussed. Furthermore, a brief view of the cloud security regulatory bodies and compliance have also been presented. Despite the research efforts in cloud security field, there are still some open research problems and challenges which are discussed in this paper.